Genotype in BRCA‐associated Breast Cancers. Issue 1 (10th December 2012) - Meric‐Bernstam, Funda; Gutierrez‐Barrera, Angelica M.; Litton, Jennifer; Mellor‐Crummey, Lauren; Ready, Kaylene; Gonzalez‐Angulo, Ana Maria; Lu, Karen H.; Hortobagyi, Gabriel N.; Arun, Banu K.
Abstract Women with BRCA1 or 2 mutations are at high risk for breast cancer. For BRCA1, a trend of increasing risk has been associated with increasing downstream (3′) location for mutations compared to the upstream (5′) mutations in the gene. For BRCA2, an increased risk of breast cancer has been associated with mutations outside of the ovarian cancer cluster region (OCCR). We sought to determine the mutation position in BRCA‐associated breast cancers and whether or not there was a genotype‐phenotype correlation. Breast cancer patients with BRCA1/2 mutations were identified by a search of a prospectively maintained data base. Mutation site, patient, and tumor characteristics were determined through retrospective review. One hundred and sixty‐four patients with BRCA1‐associated breast cancer and 109 patients with BRCA2‐associated breast cancer were identified. Among patients with BRCA1‐associated cancers, 86 (52%) had mutations in the 5′ half of the gene. Among patients with BRCA2‐associated breast cancers, 40 (37%) had OCCR mutations. Although BRCA1‐associated tumors were more likely to be ER/PR‐ than BRCA2‐associated cancers (p < 0.0001), there was no difference in the tumor characteristics among BRCA1 or BRCA2‐associated cancers based on mutation location. In this single‐institution study, over half of BRCA1‐associated and over a third of BRCA2‐associated breast cancers were associated with putative lower risk mutations. Although we cannot exclude the possibility that mutations in these regions confer a lower relative risk for breast cancer, vigilance in cancer screening and prevention remains necessary. Further studies in genotype/phenotype correlation are needed to individualize prevention strategies.